Polyphenols-rich extract from Pleurotus eryngii with growth inhibitory of HCT116 colon cancer cells and anti-inflammatory function in RAW264.7 cells. Issue 3 (21st February 2018) - Hu, Qiuhui; Yuan, Biao; Xiao, Hang; Zhao, Liyan; Wu, Xian; Rakariyatham, Kanyasiri; Zhong, Lei; Han, Yanhui; Muinde Kimatu, Benard; Yang, Wenjian
Abstract : Edible mushrooms are rich sources of bioactive components. Abstract : Edible mushrooms are rich sources of bioactive components. In this study, a polyphenol-rich extract, designated as PPEP, was isolated from an edible mushroom, Pleurotus eryngii . Using ultra high performance liquid chromatograph combined with triple time-of-flight mass spectrometry (UPLC-TOF/MS/MS), gallic acid monohydrate, 3-(3, 4-dihydroxyphenyl)-propionic acid, methyl gallate, syringic acid, ellagic acid and catechin were identified in PPEP. This phenolic-rich extract PPEP exhibited anti-inflammatory effect in lipopolysaccharide-stimulated RAW264.7 macrophages by inhibiting the overproduction of pro-inflammatory mediators including nitric oxide (NO) and reactive oxygen species (ROS). It was demonstrated that the anti-inflammatory effects of PPEP were associated with the inhibition of iNOS expression, suppression of p-IκB protein expression and inhibition of NF-κB and IκB mRNA expression. Next, the inhibitory effect of PPEP against human colon cancer cells was also determined. PPEP suppressed cell proliferation of human colon cancer HCT116 cells in a dose- and time-dependent fashion, while it showed no inhibitory effect on normal human colonic myofibroblasts CCD-18Co cells at the same tested concentrations (0–200 μg mL −1 ). Moreover, PPEP induced cell cycle arrest and led to extensive cellular apoptosis in human colon cancer cells, which was associated with the downregulation of cell cycle-related signaling protein, e.g. cyclin B and cyclin E, and the upregulation of apoptosis-related signaling protein caspase-3 and cleaved caspase-3. Overall, our results provided a basis for using PPEP as a promising preventive agent against inflammatory disease and colon cancer.